Implementation of PAI Learning Independent Learning Curriculum in Karangjati Kasihan State Elementary School - Wulandari, Nyimas; Yunita, Laili (Universitas Muhammadiyah Surakarta, 2023)
The independent learning curriculum is a curriculum designed by the government to provide convenience and freedom to schools and PAI teachers in exploring the abilities of students which are then adjusted to their resources and resources. In addition to providing freedom to teachers in exploring the abilities of students, it also provides opportunities for educators to provide material to be more organized. In the PAI independent curriculum, the most important thing is to provide the widest possible space for students so that teachers can know the potential possessed by students so that they will get maximum educational results. This study aims to examine educators in applying this independent learning curriculum into religious subjects. In this writing the author uses methods of observation, interviews, documentation. The results obtained from this study, it was explained that the implementation of the PAI curriculum in independent learning at SD Negeri Karang jati had run properly, namely educators still taking material from the Merdeka Mengajar application to facilitate the learning process, educators guided students in the learning process through discussions, problem solving and demonstrations so that This independent learning curriculum is very suitable when compared with PAI learners even though PAI teachers still need guidance in the curriculum implementation process.